Tarikat and Cemaat in Modern Day Turkey. - Ioannis Mazis (Defensor Pacis, 2000)
What is a Tarikat? What is their role in Turkey? To answer these questions the terms “Tarikat” (Islamic order) and “Cemaat” (Islamic community or group) and the differences between them will have to be clarified. Then their political and social functions will be illustrated.